The Impact of Digital-Based Mind Map on Creative Thinking Skills in Civic Education Learning - Syahputri, Neillisa Regga; Murdiono, Mukhamad (Jurnal Pendidikan Indonesia, 2022)
Students' creative thinking skills are low when using conventional learning media. Thus, the civic education learning process requires innovative learning media such as a digital-based mind map to improve students' creative thinking skills. This study analyzed the effect of digital-based mind map media on tenth-grade students' creative thinking skills in learning civic education at Vocational High School. This research was a quasi-experimental study with a quantitative approach. Data collection used to pretest and post-test. Hypothesis testing used t-test analysis with a significance level of 5%. The sample was determined through a random sampling technique totalling 62 students divided into two classes. The results showed that the score in the post-test was more significant than 9.790, and the ttable at df 60 was 2,000, and a significance value of 0.000 was smaller than the significance level of 5% (0.000 <0.05). Therefore, it can be concluded that there was a significant effect of digital-based mind map media on the creative thinking ability of tenth-grade students in learning civic education at Vocational High School.